A versatile electrospun polylactic acid nanofiber membrane integrated with halloysite nanotubes for indoor air purification, disinfection, and photocatalytic degradation of pollutants - Lou, Yaoyuan; Wang, Bin; Ma, Jiayu; Yang, Renfeng; Jin, Xu; Liu, Fang; Yang, Mengjuan; Sun, Zhiming; Li, Xiuyan; Zhang, Xiuqin (Separation and purification technology, 2023)
•A nanoclay/polymer photocatalytic electrospun nanofiber membrane was fabricated.•HNTs improve the filtration performance and lifetime for PMs by storing charges.•HNTs inhibit the aggregation of nano-Ag3PO4 and accelerate photocatalytic reaction.•The utilization of nanoclay loaded photocatalyst in air purification was realized.•Both great quality and mass production are accomplished by upgrading machine. Electrospinning nanofiber membranes (ENMs) have been studied extensively as high-efficient air filters, but still subject to low filtration efficiency for submicron PMs and limited function. Meanwhile, filters based on ENMs originated from petroleum seriously increase the burden on the environment. Polylactic acid (PLA), a bio-based biodegradable polymer with non-biotoxicity, degradability, and environmental sustainability, is a highly promising material from air purification perspectives. However, it is still a challenge to improve the air filtration performance, disinfection, and formaldehyde degradation of PLA ENMs simultaneously. Here, we feasibly present a versatile PLA ENMs integrated with natural electret halloysite nanotubes (HNTs) and silver phosphate (Ag3PO4) via the electrospinning assisted with spraying technology and continuous winding device. The HNTs improves the free-standing properties of the PLA ENMs and endows it with electret effect, which can enhance the electrostatic interaction with submicron PMs and bacteria as well as extend the service life. Furthermore, Ag3PO4 was distributed onto HNTs and then incorporated into PLA nanofiber which enables HNTs@Ag3PO4/PLA ENMs to display a remarkable disinfection and good photodegradation ability towards gaseous formaldehyde. Additionally, the HNTs@Ag3PO4/PLA ENMs exhibits excellent photodegradation ability towards methylene blue and tetracycline under the visible light irradiation, effectively solving the problems such as difficult separation and recovery of powdery photocatalysts. Such PLA based composite membrane with enhanced electrostatic interaction and photocatalytic property could show the versatilities, e.g. improving the efficiencies and service life on filtering PMs, killing bacteria, degrading VOCs, etc., which provides a new idea and feasible method for purifying indoor air and water based on green polymer and electrospinning technology.